Comparison of polyclonal expansion methods to improve the recovery of cervical cytobrush-derived T cells from the female genital tract of HIV-infected women - Bere, Alfred (Elsevier, 2010)
Cervical cytobrushing is a useful and non-invasive method for obtaining mucosal mononuclear cells from the female genital tract, but yields few cells. The aim of this study was to compare in vitro expansion protocols (anti-CD3, anti-CD3/CD28 or Dynal anti-CD3/CD28 beads) and cytokine combinations (IL-2, IL-7 and IL-15) to improve cervical T cell yields and viability. Eighteen HIV-infected women were included in this study to compare methods for polyclonal expansion of T cells from the female genital tract and blood. Comparison of T cell yields, viability and maturational status (by differential staining with CD45RO, CCR7 and CD27) was determined following 7 days of in vitro expansion. Anti-CD3 and IL-2 resulted in a 4.5-fold (range 3.7–5.3) expansion of cervical CD3+ T cells in 7 days compared to day 0. Inclusion of anti-CD28 or addition of IL-7 and IL-15 to this combination did not improve expansion. Culturing cells with Dynal beads (1:1) and IL-2, IL-7 and IL-15 gave rise to the highest yields after 7 days in both blood (7.1-fold) and cervix (5.6-fold). While expansion with anti-CD3 led to the accumulation of effector memory T cells (CD45RO+CCR7−CD27−), expansion with Dynabeads selected for accumulation of central memory T cells (CD45RO+CCR7+CD27+). We conclude that in vitro expansion with Dynabeads (1:1) in the presence of IL-2, IL-7 and IL-15 resulted in the greatest increase in viable T cells from both blood and cytobrush. Irrespective of the expansion method used, the T cell memory profile was altered following expansion.